Jawabanmu

2014-06-19T09:57:55+07:00
.> a+b = - \frac{c}{a}
    a+b =  \frac{1}{3}

.> a.b =  \frac{c}{a}
    a.b = \frac{2}{3}

jadi (a+b)^{2} + ab = (\frac{1}{3})^{2}  \frac{2}{3} = 5/9
2014-06-19T10:12:41+07:00
 3x^{2} -x+2=0

 \alpha dan  \beta  adalah akar-akar persamaan kuadrat, maka berlaku:
 \alpha + \beta = \frac{-b}{a} =\frac{-(-1)}{3}= \frac{1}{3}
 \alpha . \beta = \frac{c}{a} =\frac{2}{3}

Maka:
( \alpha + \beta ) ^{2}+ \alpha  \beta =( \frac{1}{3})^{2} + \frac{2}{3} =  \frac{1}{9} +\frac{2}{3}= \frac{7}{9}

Sekian, semoga membantu :)